PENGARUH SELF EFFICACY, TALENT MANAGEMENT, DAN PELATIHAN TERHADAP KINERJA DIMEDIASI MOTIVASI PADA KARYAWAN LEMBAGA PENYIARAN RADIO SWASTA DI KOTA PADANG - Cici Lestari; Jhon Veri; Lusiana (Halu Oleo University, 2025)
This study aims to examine the effect of self-efficacy, talent management, and training on performance mediated by motivation. A quantitative approach with hypothesis testing techniques was used in this study. There are 98 samples with the saturated sample technique, namely all employees of private radio broadcasting institutions in Padang City, West Sumatra Province. Data were collected through distributing questionnaires online and processed using SmartPLS 4.0 software with structural equation modelling techniques. The results found that self-efficacy, talent management, and training each had a positive and significant effect on motivation. Self-efficacy, talent management, and motivation each have a positive and significant effect on performance, but training was found to have an insignificant effect. The effect of self-efficacy, talent management, and training, respectively, on performance through the mediation of motivation was found to be positive and significant. The implications of the study emphasise the importance of maintaining the morale and integrity of employees in broadcasting institutions in order to produce good-quality work.